Sociotechnical Factors Influencing Unsafe Use Of Hospital Information Systems:A Qualitative Study In Malaysian Government Hospitals - Salahuddin, Lizawati; Raja Ikram, Raja Rina; Ismail, Nor Haslinda; Naim @ Mohayat, Mohd Hariz; Hashim, Ummi Rabaah; Ismail, Zuraini (SAGE Publications Ltd, 2018)
The objective of this study is to identify factors influencing unsafe use of hospital information systems in Malaysian government hospitals.Semi-structured interviews with 31 medical doctors in three Malaysian government hospitals implementing total hospital information systems were conducted between March and May 2015.A thematic qualitative analysis was performed on the resultant data to deduce the relevant themes.A total of five themes emerged as the factors influencing unsafe use of a hospital information system:(1)knowledge,(2)system quality,(3) task stressor,(4) organization resources,and (5) teamwork.These qualitative findings highlight that factors influencing unsafe use of a hospital information system originate from multidimensional sociotechnical aspects.Unsafe use of a hospital information system could possibly lead to the incidence of errors and thus raises safety risks to the patients.Hence,multiple interventions (e.g. technology systems and teamwork) are required in shaping high-quality hospital information system use.